Predictors of adverse pathologic features after radical prostatectomy in low-risk prostate cancer - Park, Jae Won (BMC Cancer, 2018)
BACKGROUND: Prostate-specific antigen (PSA) screening more frequently detects early stage prostate cancer (PC). However, adverse pathologic features (APFs) after radical prostatectomy (RP) in low-risk PC occur. Previous related studies had utilized outdated staging criteria or small sample cohorts. In this study, we analyzed predictors of APFs after RP in low-risk PC using classification under the current criteria. MATERIALS AND METHODS: We retrospectively reviewed medical records of 546 low-risk PC patients who had undergone RP. Low-risk PC was defined as PC with clinical T1–T2a, Gleason score ≤ 6, and PSA levels < 10 ng/mL. Clinical and pathological parameters were analyzed to predict APFs. APFs were defined as extracapsular extension (ECE), seminal vesicle invasion (SVI), or positive surgical margins (PSM). We analyzed our data using univariable and multivariable logistic regression analyses, as well as receiver operator characteristics to predict APFs. RESULTS: Among 546 patients, ECE, SVI, and PSM were present in 199 (36.4%), 8 (1.5%), and 179 cases (32.8%), respectively. PSM had a significant correlation with preoperative high PSA levels and number of positive cores obtained. ECE/SVI was also significantly correlated with PSA levels and number of positive cores. As a result, presence of APFs after RP was associated with high PSA levels and large number of positive cores. PSA > 4.5 ng/mL and number of positive cores > 2 in low-risk PC were significantly associated with APFs, and suggested as cut-off values for predicting APFs. CONCLUSIONS: PSA > 4.5 ng/mL and number of positive cores > 2 in low-risk PC were associated with presence of APFs and patients with such records should be considered carefully to provide active surveillance. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12885-018-4416-4) contains supplementary material, which is available to authorized users.